To solve this problem, let's first define the variables based on the given information:
- Let \( a \) be Tony's current age.
- Since Andrea is 6 years younger than Tony, her current age is \( a - 6 \).
In two years:
- Tony's age will be \( a + 2 \).
- Andrea's age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony will be three times as old as Andrea: \[ a + 2 = 3(a - 4) \]
Now let's match this with the options given:
- \( a + 2 = 3(a - 6 + 2) \) simplifies to \( a + 2 = 3(a - 4) \). This is correct.
- \( 3(a + 2) = a - 6 + 2 \) simplifies to \( 3(a + 2) = a - 4 \). This is incorrect.
- \( a = 3(a + 2) \) is incorrect.
- \( a + 2 = 3(a + 6 + 2) \) is incorrect.
The correct answer is: \( a + 2 = 3(a - 6 + 2) \)